Visualisasi Mitologi Kala Rahu "Candra Graha" sebagai Tema dalam Penciptaan Karya Tari yang Berpijak pada Tari Legong - Ida Bagus Ketut Sudiasa; Tuteng Suwandi; Khalifaturrahman, Putri Maulida (Jurnal Pendidikan Tari, 2022)
This research was conducted to produce data on Balinese people's beliefs in the mythology of Kala Rahu, the mythology of Kala Rahu will be represented through a form of dance visualization that reviews the lunar eclipse which tells of each event that there is a meeting between Kala Rahu and Dewi Ratih. This research uses a qualitative research type with a phenomenological approach. . The method used in the creation of this dance work is the “Moving from Within: A New Method for Dance Making” method based on a book that has been translated by I Wayan Dibia entitled Moving According to the Heart. The stages of taking the motion steps used are based on the elements of daily movement and the Legong dance. The daily movements taken are like playing. The movement of the Legong dance, the Legong dance has several motion motifs, the motion motifs taken include agem, ulap-ulap, ngeseh, ngumbang. Candra Graha's work is packaged in a dance film shooting video format that makes it easy for the audience to see from various points of view, which will be broadcast online. By choosing to use two dancers with various roles, children, grandmothers, Dewi Ratih, Kala Rahu, Batara Guru, and Batara Narada. The selection of dancers includes the uniformity of posture in the roles performed and the dancer's movement techniques. Results The conclusion from the research can be to carry out motion exploration activities using the data that has been obtained.